Turn of the Century - Jackson, Ellen B. (Watertown, MA : Charlesbridge Publishing, 1998)
Children living in Great Britain and the United States at the beginning of each century between 1000 and 2000 A.D. describe their lifestyle at the time.
Bluebonnet 1999-2000